Visual media coding and transmission - Kondoz, A. M., (Ahmet M.); IEEE Xplore (Online Service); Wiley ([Piscataqay, New Jersey] : IEEE Xplore, 2009)
This book presents the state-of-the-art in visual media coding and transmission Visual Media Coding and Transmission Transmission is an output of VISNET II NoE, which is an EC IST-FP6 collaborative research project by twelve esteemed institutions from across Europe in the fields of networked audiovisual systems and home platforms. The authors provide information that will be essential for the future study and development of visual media communications technologies. The book contains details of video coding principles, which lead to advanced video coding developments in the form of Scalable Coding, Distributed Video Coding, Non-Normative Video Coding Tools and Transform Based Multi-View Coding. Having detailed the latest work in Visual Media Coding, networking aspects of Video Communication is detailed. Various Wireless Channel Models are presented to form the basis for both link level quality of service (QoS) and cross network transmission of compressed visual data. Finally, Context-Based Visual Media Content Adaptation is discussed with some examples. Key Features: . Contains the latest advances in this important field covered by VISNET II NoE . Addresses the latest multimedia signal processing and coding algorithms . Covers all important advance video coding techniques, scalable and multiple description coding, distributed video coding and non-normative tools . Discusses visual media networking with various wireless channel models . QoS methods by way of link adaptation techniques are detailed with examples . Presents a visual media content adaptation platform, which is both context aware and digital rights management enabled . Contains contributions from highly respected academic and industrial organizations Visual Media Coding and Transmission will benefit researchers and engineers in the wireless communications and signal processing fields. It will also be of interest to graduate and PhD students on media processing, coding and communications courses.
10.4.2 Test for the EDGE System 443 -- 10.4.3 Test for the UMTS System 445 -- 10.4.4 Tests for the EDGE-to-UMTS System 445 -- 10.5 Conclusions 452 -- References 453 -- 11 Context-based Visual Media Content Adaptation 455 -- 11.1 Introduction 455 -- 11.2 Overview of the State of the Art in Context-aware Content Adaptation 457 -- 11.2.1 Recent Developments in Context-aware Systems 457 -- 11.2.2 Standardization Efforts on Contextual Information for Content Adaptation 467 -- 11.3 Other Standardization Efforts by the IETF and W3C 476 -- 11.4 Summary of Standardization Activities 479 -- 11.4.1 Integrating Digital Rights Management (DRM) with Adaptation 480 -- 11.4.2 Existing DRM Initiatives 480 -- 11.4.3 The New ''Adaptation Authorization'' Concept 481 -- 11.4.4 Adaptation Decision 482 -- 11.4.5 Context-based Content Adaptation 488 -- 11.5 Generation of Contextual Information and Profiling 492 -- 11.5.1 Types and Representations of Contextual Information 492 -- 11.5.2 Context Providers and Profiling 494 -- 11.5.3 User Privacy 497 -- 11.5.4 Generation of Contextual Information 498 -- 11.6 The Application Scenario for Context-based Adaptation of Governed Media Contents 499 -- 11.6.1 Virtual Classroom Application Scenario 500 -- 11.6.2 Mechanisms using Contextual Information in a Virtual Collaboration Application 502 -- 11.6.3 Ontologies in Context-aware Content Adaptation 503 -- 11.6.4 System Architecture of a Scalable Platform for Context-aware and DRM-enabled Content Adaptation 504 -- 11.6.5 Context Providers 507 -- 11.6.6 Adaptation Decision Engine 510 -- 11.6.7 Adaptation Authorization 514 -- 11.6.8 Adaptation Engines Stack 517 -- 11.6.9 Interfaces between Modules of the Content Adaptation Platform 544 -- 11.7 Conclusions 552 -- References 553 -- Index 559.
Includes bibliographical references (p. 553-558) and index.
Also available in print.
Mode of access: World Wide Web
Description based on PDF viewed 10/24/2017.
Keywords: Multimedia communications; Video compression; Coding theory; Data transmission systems; Electronic books